An Application of The Sustainable Transformational Leadership Dimensions on Teacher’s Performance: A Social Network Analysis - Aymen AL Qaradaghi; Razan Kerkukli; Riazuddin Ahmed (الأستاذ)
Teacher’s performance is one of the arguable issues in the organization. Sustainable Transformational leadership and its dimensions play a big role to change the nature of teacher’s performance in the organization. In this study, sustainable transformational leadership dimensions were discussed and examined through social network analysis SNA as a tool to analyze and understand results. Data collection were conducted and 30 respondents participated in the questionnaire. Organizations are educational sectors and they are 3 organizations and mentioned as symbols in the study. This study, shows that both sustainable occupational training SOT and sustainable social training SST as dimensions of sustainable transformational leadership approach able to enhance and engage teachers if the method of applying the dimensions is correct to keep improving sustainably. Organizations A and B are positive regarding the SOT and SST; however, organization C is negative regarding the SOT and SST.